2024
DOI: 10.3390/biomedicines12040837
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Imaging Findings of Adrenal Abnormalities in TAFRO Syndrome: A Systematic Review

Ryo Kurokawa,
Akira Baba,
Rui Kano
et al.

Abstract: This systematic review article aims to investigate the clinical and radiological imaging characteristics of adrenal abnormalities in patients with thrombocytopenia, anasarca, fever, reticulin fibrosis, renal dysfunction, and organomegaly (TAFRO) syndrome. We searched the literature in PubMed, the Cochrane Library, and the Web of Science Core Collection. Ultimately, we analyzed 11 studies with 22 patients plus our 1 patient, totaling 23 patients. The mean age was 47.0 ± 12.6 years. There were 20 male and 3 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In collections of case studies, patients observed to have TMA-like renal injury patterns tended to have earlier renal biopsies relative to those patients who had an MPGN pattern of injury, suggesting that MPGN lesions may result from chronic TMA lesions [ 64 ]. Peri-renal injury patterns specific to iMCD-TAFRO patients have also been observed, including adrenal hemorrhage and adrenal ischemia [ 65 ]. Further research is required regarding a potential concurrent role for VEGF in peri-renal injury manifestations.…”
Section: The Role Of Vegf In Pathophysiology Of Tafro Syndromementioning
confidence: 99%
“…In collections of case studies, patients observed to have TMA-like renal injury patterns tended to have earlier renal biopsies relative to those patients who had an MPGN pattern of injury, suggesting that MPGN lesions may result from chronic TMA lesions [ 64 ]. Peri-renal injury patterns specific to iMCD-TAFRO patients have also been observed, including adrenal hemorrhage and adrenal ischemia [ 65 ]. Further research is required regarding a potential concurrent role for VEGF in peri-renal injury manifestations.…”
Section: The Role Of Vegf In Pathophysiology Of Tafro Syndromementioning
confidence: 99%